Acute Effect of Cigarette Smoking on Pupil Size and Ocular Aberrations: A Pre- and Postsmoking Study - Uzeyir Erdem; Fatih C. Gundogan; Umut Aslı Dinc; Umit Yolcu; Abdullah Ilhan; Salih Altun (Journal of Ophthalmology)
Aim. To evaluate the acute effects of cigarette smoking on photopic and mesopic pupil sizes and wavefront aberrations. Methods. Cigarette smoker volunteers were recruited in the study. Photopic and mesopic pupil sizes and total ocular aberrations were measured before smoking and immediately after smoking. All volunteers were asked to smoke a single cigarette containing 1.0 mg nicotine. Pupil sizes and total ocular aberrations were assessed by optical path difference scanning system (OPD-Scan II ARK-10000, NIDEK). Only the right eyes were considered for statistical analysis. The changes of pupil size and total ocular aberrations after smoking were tested for significance by Wilcoxon signed ranks test. Results. Mean photopic pupil size decreased from 3.52 ± 0.73 mm to 3.29 ± 0.58 mm (P=0.001) after smoking. Mean mesopic pupil size was also decreased from 6.42 ± 0.75 mm to 6.14 ± 0.75 mm after smoking (P=0.001). There was a decrease in all the measured components of aberrations (total wavefront aberration, higher-order aberration, total coma, total trefoil, total tetrafoil, total spherical aberration and total higher-order aberration) after smoking; however the differences were insignificant for all (P>0.05). Conclusion. Our results indicate that pupil constricts after smoking. On the other hand, smoking does not alter ocular aberrations.